2012
DOI: 10.1128/jcm.00337-12
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Abbott RealTi m e High-Risk Human Papillomavirus (HPV), Roche Cobas HPV, and Hybrid Capture 2 Assays to Direct Sequencing and Genotyping of HPV DNA

Abstract: bInfection with high-risk (HR) human papillomavirus (HPV) genotypes is an important risk factor for cervical cancers. We evaluated the clinical performances of two new real-time PCR assays for detecting HR HPVs compared to that of the Hybrid Capture 2 test (HC2). A total of 356 cervical swab specimens, which had been examined for cervical cytology, were assayed by Abbott RealTime HR and Roche Cobas HPV as well as HC2. Sensitivities and specificities of these assays were determined based on the criteria that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 35 publications
4
35
2
Order By: Relevance
“…Cross-reactions with nononcogenic HPV genotypes (10,11) have also been shown for the hc2 assay. Contrary to our results, Park et al (12) showed a higher proportion of samples that were positive by the hc2 test and negative by the cobas test, as well as a higher positivity rate for the hc2 test than the cobas test; Wong et al (13) showed a higher confirmation rate by the Linear Array test for the hc2 test than for the cobas test.…”
contrasting
confidence: 54%
“…Cross-reactions with nononcogenic HPV genotypes (10,11) have also been shown for the hc2 assay. Contrary to our results, Park et al (12) showed a higher proportion of samples that were positive by the hc2 test and negative by the cobas test, as well as a higher positivity rate for the hc2 test than the cobas test; Wong et al (13) showed a higher confirmation rate by the Linear Array test for the hc2 test than for the cobas test.…”
contrasting
confidence: 54%
“…This is in contrast to a previous study, which compared the HC2 and cobas assay using ThinPrep preparation and reported a higher sensitivity with the HC2 assay. 12 One difference in the prior study is that all specimens were collected in PreservCyt transport medium, whereas only a minority of cases were collected in PreservCyt solution in the present study. Another notable difference between the previous and our current study is that the specimens were stored at À708C for unknown durations before being tested in the former study, whereas the specimens in the present study were stored at room temperature and were analyzed within 1 week after collection.…”
Section: Commentmentioning
confidence: 81%
“…20 Based on the ATHENA study, a slightly higher positive hrHPV rate was also noted with the cobas assay compared with the HC2 assay (32.6% versus 31.5%) among women with atypical squamous cells of undetermined significance, 14 whereas other studies observed a higher positive hrHPV rate with the HC2 assay compared with the cobas assay in specimens collected with Preservcyt Solution (Hologic). [10][11][12] Approximately 80% (7 of 9) of HC2-positive/cobasnegative cases tested positive for low-risk HPV only by LA whereas 13.3% (4 of 30) of cobas-positive/HC2-negative cases did. This difference was statistically significant.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…They found a strong agreement between the cobas 4800 HPV test and HC2 (97.3% and 98.3% for controls and cases, respectively. Similarly, Park et al, [29] demonstrated, with HC2, a sensitivity of 96.6% with a specificity of 89.1% for detecting HR HPVs, while, with Cobas, they were 91.7% and 97.0%, respectively, thus very close. These 2 studies involved a relatively small sample (less than 1000 and 356 respectively).…”
Section: Citation: Desplechain C De Mouzon J Benkhalifa M Cartolanmentioning
confidence: 98%